ON ESTIMATES OF LOWER AND UPPER LIMITS FOR THE MASSES OF COMPACT COMPONENTS IN CLOSE BINARIES - Beskin, G.; Borisov, N.; Pustil'nik, L. (Одеські астрономічні публікації, 2017)
A method of the determination of limits for a compact component mass on the base of disk emission lines parameters is described. Lower limit of mass depends upon the distance between maxima in double peaked lines, upper upon full width of line. The method is tested for some cataclysmic variables with well-known masses of compact components. It is obtained a lower limit for the mass of the compact object in the close binary SS 433 is 4.9M☉. This component apparently is a black hole.